Obtenção de extratos de resíduos de laranja utilizando diferentes metodologias de extração - Muller, Érika Nogueira (2023)
Globally, significant amounts of orange waste are incorrectly disposed of in the environment. Orange residual oil is a potential source of compounds of interest and important alternatives with high extraction yields have been explored. Appropriately, this study investigated the effects of oil extraction processes involving (PLE) pressurized liquid extraction and (SFE-CO2) supercritical fluid extraction with CO2 on orange residues. The results were compared with the standard Soxhlet procedure. The evaluation of the operational parameters was established based on the adjustment of different process conditions for pressure (150 and 350 MPa), reaction time (20 and 60 minutes), and temperature (40 and 60 ºC). For the PLE extraction, distinct ethanol/distilled water proportiuons (50/50, 25/75, and 0/100, w/w) were investigated. The results indicated that the maximum oil yields for orange peel and pomace were 37.76% and 43.39%, respectively, for the PLE method. The SFE-CO2 method expressed maximum yields of 0.50% and 0.38% for peel and pomace, respectively. The GC-MS analysis reported the concentration of bioactive compounds after the distinct extraction methods such as citronella, limonene, among others. The optimization of operational parameters made it possible to establish criteria that express better oil yields and profitable technologies to add value to plant residues.